استراتيجية مقترحة لتطبيق التدريب المدمج بالأكاديمية المهنية للمعلمين فى ضوء متطلبات مجتمع المعرفة: دراسة ميدانية - عبدالنعيم، محمد جاد أحمد Abdulnaeem, Mohammed Jad Ahmed (جامعة سوهاج - كلية التربية, 2018)
هدفت الدراسة التعرف إلى مفهوم التدريب المدمج وأهميته واستراتيجية تطبيقه في دعم التنمية المهنية من قبل الأكاديمية، كما هدفت الكشف عن المعوقات التي تواجه الأكاديمية لتبني التدريب المدمج كاستراتيجية متطورة في ضوء مجتمع المعرفة، بالإضافة إلى التعرف إلى واقع تطبيق الأكاديمية للتدريب المدمج لأعضاء هيئة التعليم العام المصري في ضوء مجتمع المعرفة، كما هدفت إلى صياغة استراتيجية مقترحة لتطبيق الأكاديمية للتدريب المدمج كاتجاه لدعم التنمية المهنية للعاملين بالتعليم العام في مصر في ضوء متطلبات مجتمع المعرفة، واستخدمت الدراسة المنهج الوصفي، كما اعتمدت على استبانة طبقت على عينة ممثلة من المدربين بلغت (270) مدربا في أثناء عملهم بفروع الأكاديمية المهنية للمعلمين، وتوصلت الدراسة إلى مجموعة من المتطلبات الخاصة لتطبيق استراتيجية التدريب المدمج ومنها: - تغيير الثقافة التنظيمية والإدارية داخل الأكاديمية المهنية للمعلمين بما يشجع على تطبيق التدريب المدمج. - توظف الأكاديمية المهنية للمعلمين استراتيجيات التدريب المدمج في النشاطات التدريب المختلفة التي تطبق ببرامج التنمية المهنية المستدامة لأعضاء هيئة التعليم العام المصري. - تتعاقد الأكاديمية المهنية للمعلمين مع الفنيين المتخصصين في مجال الحاسب الآلي والبرمجة والشبكات والإنترنت. - تسعى الأكاديمية المهنية للمعلمين لعقد برتوكولات تعاون مع المراكز البحثية والكليات المتخصصة-نظم المعلومات؛ لتستفيد من جهود الخبراء في مجال استراتيجيات التدريب المدمج. - وضع معايير ومؤشرات علمية لاختيار المدريين ومهندسي الصيانة؛ لتطبيق التدريب المدمج بالأكاديمية المهنية للمعلمين. - توفير الدعم المالي لشراء موقع تدريبي عبر شبكة الإنترنت يسمح بالدمج بين التدريب التقليدي والتدريب الإلكتروني.
The professional teacher's academy the study aimed to the concept of pressed education it's importance and the strategy of it application in supporting the professional development by the academy and also it aimed to reveal the hinders which face the academy to build the pressed training a developed strategy in the light of the society in the light of the society of knowledge as well as identifying the fact of the academy applying of the pressed training for the members of the Egyptian public teaching staff in the light of the society of knowledge and it aimed to from a suggested strategy for the academy applying of the pressed training as a trend for supporting the professional development for the employees of the Egyptian public education in the light of the requirements of the society of knowledge, the study the descriptive curriculum, and also depended on a questionnaire applied on a sample of trainer switch reached about (270) trainers during their work in the branches of the professional academy for teacher's and the study reached a group of special requirements for applying the pressed training strategy and of it: - Changing the systematic and administrative culture inside the professional a academy for teacher's which encourages applying pressed training the professional academy for teachers functions the pressed training strategies in the different training activities while are applied for the permanent professional development programmes for members of the Egyptian public education. - The professional academy for teachers make contracts with the specialized technicians in the field of computers, programming, website and the internet. - The professional academy for teacher's looks for making. - Co-operation agreements with the research centers and the specialized colleges. - The information systems, to make use of benefit from the efforts of the experts in the field of the pressed training setting scientific Roderick's and signs for choosing the trainers and engineers of maintenance to apply the pressed. - Education for teachers professional academy providing the financial supply for buying a training website on the internet to allow pressing the traditional with the electronic training.
Keywords: الاستراتيجية -- التنمية المهنية -- التدريب المدمج -- الأكاديمية المهنية للمعلمين -- مجتمع المعرفة